The supramolecular structure of bone: X‐ray scattering analysis and lateral structure modeling. Issue 9 (1st September 2016) - Zhou, Hong-Wen; Burger, Christian; Wang, Hao; Hsiao, Benjamin S.; Chu, Benjamin; Graham, Lila
Abstract : The first interpretable X‐ray scattering data concerning lateral (radial) packing of bone collagen molecules is presented, which indicates that bone contains spatially discrete collagen microfibrils. A spatially discrete microfibril model supports structure–function‐based explanations for internal fibril mineralization and for the unique pattern of collagen post‐translational modifications in mineralized tissues. Abstract : The evolution of vertebrates required a key development in supramolecular evolution: internally mineralized collagen fibrils. In bone, collagen molecules and mineral crystals form a nanocomposite material comparable to cast iron in tensile strength, but several times lighter and more flexible. Current understanding of the internal nanoscale structure of collagen fibrils, derived from studies of rat tail tendon (RTT), does not explain how nucleation and growth of mineral crystals can occur inside a collagen fibril. Experimental obstacles encountered in studying bone have prevented a solution to this problem for several decades. This report presents a lateral packing model for collagen molecules in bone fibrils, based on the unprecedented observation of multiple resolved equatorial reflections for bone tissue using synchrotron small‐angle X‐ray scattering (SAXS; ∼1 nm resolution). The deduced structure for pre‐mineralized bone fibrils includes features that are not present in RTT: spatially discrete microfibrils. The data are consistent with bone microfibrils similar to pentagonal Smith microfibrils, but are not consistent with the (nondiscrete) quasi‐hexagonal microfibrils reported for RTT. These results indicate that collagen fibrils in bone and tendon differ in their internal structure in a manner that allows bone fibrils, but not tendon fibrils, to internally mineralize. In addition, the unique pattern of collagen cross‐link types and quantities in mineralized tissues can be can be accounted for, in structural/functional terms, based on a discrete microfibril model.